A review of the infrageneric classifications proposed for Kalanchoe (Crassulaceae subfam. Kalanchooideae) from the earliest times up to 2000 - Smith, Gideon F. (Phytotaxa, 2023)
The infrageneric classifications, especially at the ranks of subgenus, section, and subsection proposed for Kalanchoe (Crassulaceae subfam. Kalanchooideae) from the early 1800s up to the end of the 20th century, are analysed. The pertinent works of especially Haworth (1820s); Baillon (1880s); Raymond-Hamet, Koorders, and Berger (all three from the early 1900s to 1930s); Boiteau and as elaborated on by Boiteau and Mannoni (1940s); Raymond-Hamet and Marnier-Lapostolle (1960s); Maire (1970s); and Boiteau and Allorge-Boiteau (1990s) are assessed to clarify the use of infrageneric ranks by these authors. From this analysis of the infrageneric classification of Kalanchoe during a period of about 250 years, it is evident that, with the exception of: (1) one validly published unranked name published by Baillon in 1885; (2) one subgenus name validly published by Koorders in 1919; (3) several unranked names validly published by Alwin Berger in 1930; and (3) two new combinatons validly published by Boiteau in 1947 at the rank of section and two new combinatons validly published by Boiteau in 1947 at the rank of subsection, all other such designations that were proposed between 1 January 1935 and 1 January 1953 were not validly published. The dates 1 January 1935 (Art. 39.1 of the International Code of Nomenclature for algae, fungi, and plants [ICN], Latin requirement) and 1 January 1953 (aspects of Articles 35 and 41 of the ICN, on new combinations, names at new ranks, and replacement names) are significant in determining the valid publication of historically proposed new names and new combinations. Furthermore, all the names proposed for infrageneric groups in Kalanchoe that postdate 1 January 1953, and up to 2000, the cutoff date used in this paper, were not validly published (aspects of Art. 41 of the ICN, on new combinations, names at new ranks, and replacement names) or were proposed informally only and not intended for valid publication. Note, especially, that neither of the two infrageneric designations proposed in 1916 and 1933, respectively, by Raymond-Hamet, the undisputed authority on Kalanchoe during the 20th century, were validly published.